A case of tuberous sclerosis presenting with dysrhythmia in the first day of life - (:unkn) unknown (TURKISH J PEDIATRICS, 2004)
Cardiac rhabdomyoma (CR) is the most common primary cardiac tumor in childhood. Although CRs are asymptomatic in many cases, they may cause arrhythmia, heart failure and fetal hydrops. Babies with arrhythmia in the neonatal period must be investigated for structural heart disease including CR. Cardiac rhabdomyoma may either present as an isolated tumor or may be related with tuberous sclerosis. Arrhythmia due to CR may be the initial sign of tuberous sclerosis. We report a case of tuberous sclerosis presenting with ventricular premature beats and second-degree atrioventricular block in the first day of life who was found to have multiple CR during echocardiographic examination.
Keywords: arrhythmia in neonates; cardiac tumor; rhabdomyoma; tuberous sclerosis; CARDIAC RHABDOMYOMA; VENTRICULAR-TACHYCARDIA; TUMORS; ADULT